The Analysis of the Synoptic of the Values of Geopotential height at the Extension and Center of the Siberian High over Iraq and its Impact on Temperature and Relative humidity - Assis. Lect. Ali Najim Hussein; Prof. Dr. Ali Ghalis Nahi al-Saidi (Journal of College of Education, 2024)
The study showed that the values Geopotential height of the centers and extension of the Siberian high are increasing spatially from southern Iraq to its north due to the nature of the topographic situation, as well as the presence of a center or cell cut from the Siberian high geographically close to Iraq, which is formed on the Caspian Sea or the Anatolian Plateau to have a role in increasing its control and increasing the amounts of its voltage height, and imposes its control mostly during the cold season, so we conclude that the voltage high of the extension of the high in the three regions of Iraq (northern, central and southern) during the study period (2010-2021) recorded an average of High reached (175.8m, 163.8m and 147.3m) at the observation (00) GMT respectively, while the observation of (12) GMT recorded an average of the voltage values by (154.1 m, 142.1m and 136.5m) in the same order, As for the center of the high, it began to gradually increase and the mass of the high swelled, so its highest high was from the extension for the previously mentioned period during the two observations mentioned with pressure values of (221.3m, 181.6m), (189.9m, 165.6m) and (182.2m, 165.4m) for the three mentioned regions and according to the sequence, While the extension of the accompanying high was recorded at the level of (850) hPa for the two observations mentioned by (1555.3m, 1165.5m) and by the center of (1174.7m, 1171.2m) for the northern region and reached (1551.6 m, 1161 m) and the center of facilities (1167.3m, 1164.6m) for the central region, while the southern region recorded an extension rate of (1542.8m, 1158.8m) and a center of (1164.3m, 1161.8m) for the level referred to in the same sequence